1998
DOI: 10.1016/s0165-2427(98)00156-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibody and cytokine responses in kittens during the development of feline infectious peritonitis (FIP)

Abstract: Two recombinant FIPV spike proteins were assessed for their immunogenic properties in 8-week-old kittens, which were then challenged intranasally with FIPV 79-1146. Humoral responses were assessed by ELISA and serum neutralisation test. Changes in PBMC cytokine mRNA levels were detected by a reverse transcription, semiquantitative polymerase chain reaction assay (RT-sqPCR), assessing IL-2, IL-4, IL-6, IL-10, IL-12 and IFNgamma. All of the kittens developed clinical signs typical of FIP, which were confirmed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 68 publications
4
39
0
Order By: Relevance
“…Well number 1, molecular weight marker; 2-5, ConAstimulated feline PBMC; 6, empty; 7-10, feline PBMC without stimulation; 11,empty;[12][13][14][15]FIP cat (167/ 98) liver;16,empty;[17][18][19][20]FIP cat (167/98) lung;21,Mwmarker;22,empty;23,marker;[24][25][26][27]FIP cat (125/98) A somewhat unexpected finding was the increased expression of IFN-g within inflammatory lesions of both types, but in particular type B. In contrast, previous studies on experimentally infected cats have indicated that IFN-levels are low in these animals, accounting for a poor CMI, and thus development of disease (Gunn-Moore et al, 1998;Kiss et al, 2004). However, those results were obtained using peripheral blood mononuclear cells only.…”
Section: Discussionmentioning
confidence: 88%
“…Well number 1, molecular weight marker; 2-5, ConAstimulated feline PBMC; 6, empty; 7-10, feline PBMC without stimulation; 11,empty;[12][13][14][15]FIP cat (167/ 98) liver;16,empty;[17][18][19][20]FIP cat (167/98) lung;21,Mwmarker;22,empty;23,marker;[24][25][26][27]FIP cat (125/98) A somewhat unexpected finding was the increased expression of IFN-g within inflammatory lesions of both types, but in particular type B. In contrast, previous studies on experimentally infected cats have indicated that IFN-levels are low in these animals, accounting for a poor CMI, and thus development of disease (Gunn-Moore et al, 1998;Kiss et al, 2004). However, those results were obtained using peripheral blood mononuclear cells only.…”
Section: Discussionmentioning
confidence: 88%
“…in terminally ill cats (Pedersen, 2014a). There are several longitudinal studies which have followed the entire disease course, but these studies were concerned mainly with disease signs such as fever, antibody responses and cytokine expression and not with viral loads in various tissues (Pedersen and Boyle, 1980;Weiss and Scott, 1981;Gunn-Moore et al, 1998a). Only one other temporal study has been performed on FIPV levels in peripheral blood of experimentally infected cats (de Groot-Mijnes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, antibodies increase the viral uptake by macrophages (Hodatsu et al, 1993), while in vivo they induce immune complexes formation and deposition (Jacobse-Geels et al, 1980). During the disease a functional shift of T helper cells from Th1 to Th2 occurs (Gunn-Moore et al, 1998). The number of lymphocytes decreases in lymph nodes (Kipar et al, 2001), in the lesions (Kipar et al, 1998;Paltrinieri et al, 1998) and in blood (Sparkes et al, 1994;Pedersen, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The cause of lymphocyte depletion seems to be lymphocyte apoptosis, most likely due to the release of pro-aptoptotic factors from phagocytes (Haagmans et al, 1996). In contrast, a Th1 cytokine response (Gunn-Moore et al, 1998), and a follicular hyperplasia in lymph nodes (Kipar et al, 1999) have been reported in cats resistant to the infection. Circulating lymphocyte subsets have been analysed only in few cats with FIP and strong individual variations have been reported (Knotek et al, 2000).…”
Section: Introductionmentioning
confidence: 99%